Analysis of Environmental and Sociodemographic Factors with the Incidence of Diarrhea in Toddlers in Aceh Province in 2023 - Adawiah, Rabiatul; Susanna, Dewi (Universitas Muhammadiyah Surakarta, 2024)
Pendahuluan: Penyakit diare menjadi salah satu gangguan gastrointestinal yang sering kali terjadi pada anak usia balita. Terjadi peningkatan kasus diare balita pada tahun 2021 hingga tahun 2023 di Provinsi Aceh. Faktor lingkungan dan sosiodemografi merupakan faktor yang saling berkaitan untuk terjadinya diare pada balita. Tujuan penelitian ini yakni untuk menganalisis faktor lingkungan dan sosiodemografi dengan kejadian diare pada balita di Provinsi Aceh. Metode: Penelitian ini menggunakan desain studi cross sectional dan sumber data diperoleh dari Survei Kesehatan Indonesia (SKI) tahun 2023 dengan jumlah sampel yang dianalisis sebesar 4.234 anak usia 0-59 bulan di Provinsi Aceh. Analisis data dilakukan dengan menggunakan analisis complex samples secara univariat dan bivariat menggunakan uji Chi-Square. Hasil: Tidak ada hubungan antara variabel akses air minum (p-value=0,468, OR 0,836), sanitasi (p-value= 0,993, OR: 1.003), pengelolaan sampah (p-value= 0,381, OR: 0,751), pengelolaan limbah (p-value=0,863, OR: 0,948), pengolahan air minum (p-value= 0,477, OR: 0,835), jenis kelamin (p-value= 0,808, OR: 0,948) dan tempat tinggal (p-value= 0,769, OR: 1, 079) dengan kejadian diare pada balita. Sementara, variabel usia balita menunjukkan hubungan yang signifikan dengan kejadian diare pada balita (p-value= 0,032, OR: 1,610 (1,037-2,500). Simpulan: Ada hubungan antara usia dengan kejadian diare pada balita di Provinsi Aceh. Diperlukan kerjasama lintas sektor untuk meningkatkan peran posyandu melalui edukasi terkait tumbuh kembang anak balita serta perilaku hidup bersih dan sehat dalam lingkungan rumah tangga. Introduction: Diarrhea disease is one of the gastrointestinal disorders that often occurs in children under five years of age. There was an increase in diarrhea cases among children under five years old by 16% in 2021, 29% in 2022 and 31.7% in 2023 in Aceh Province. Environmental and sociodemographic factors are interrelated factors for the occurrence of diarrhea in toddlers. The purpose of this study was to analyze environmental and sociodemographic factors with the incidence of diarrhea in toddlers in Aceh Province. Methods: This study used a cross-sectional study design and the data source was obtained from the Survei Kesehatan Indonesia (SKI) in 2023 with a total sample size of 4,234 children aged 0-59 months in Aceh Province. Data analysis was performed using univariate and bivariate complex samples analysis using the Chi-Square test. Results: There was an association between child age and the incidence of diarrhea in children under five years of age in Aceh Province in 2023 (p-value = 0.032, OR: 1,610 (1,037-2,500). In this population, we have 95% confidence that age of the child is a risk factor for the incidence of diarrhea in children aged 0-24 months in Aceh Province with a range between 1.051-2.539. Conclusion: Children aged 0-24 months are at 1.634 times greater risk of diarrhea in children under five compared to children aged 25-59 months. Cross-sectoral cooperation is needed to improve the role of posyandu in health promotion efforts through integrated health counseling on the growth and development of children under five and education on clean and healthy living behaviors in the household environment.